INTERACTION BETWEEN CHINA AND CENTRAL ASIAN COUNTRIES, IN THE FRAMEWORK OF THE SCO: THE SOCIO-CULTURAL ASPECT (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
Projects implemented within the framework of the SCO at the present stage are notonly a tool for socio-economic rapprochement of the partner countries, but also as a mechanismof soft power policy for the PRC. This article will describe the current state of relations betweenthe PRC and Central Asian countries. The author aims to identify promising areas of China’s softpower policy in the socio-cultural dimension of the Central Asian region. The generalized experience will be used to improve the policy of China, as a member of the SCO, in relation to partnercountries.
Keywords: SCO, international organizations, socio-cultural cooperation, PRC, Russian Federation, Kazakhstan, Tajikistan, Kyrgyzstan, Uzbekistan, cultural cooperation, humanitarian cooperation, diplomacy